PENGARUH RELATIONSHIP MARKETING DAN SERVICE QUALITY TERHADAP LOYALITAS NASABAH (Studi Pada Bank BRI Kantor Kas Unisma) (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study uses quantitative research as the research design. The type of this study is explanatory research. The sample of this study were customer of BRI Bank office KAS Unisma that were 98 respondents. This study used the questionnaire as the data collection and used analysis of multiple linier regression of SPSS 24 aplication for Macbook as the method of analysis the data. The result of this study indicate that Relationship Marketing and Service Quality simultaneously influence the customer loyalty of BRI Bank office KAS Unisma. The relationship marketing has partial effect on customer loyalty of BRI Bank office KAS Unisma. However, service quality does not partially effect the customer loyalty of BRI Bank office KAS Unisma.Keywords: Relationship Marketing, Service Quality and Customer Lolalty